Senescence-Associated Gene Expression during Ozone-Induced Leaf Senescence in Arabidopsis - Miller, Jennifer D. (American Society of Plant Physiologists, 1999)
The expression patterns of senescence-related genes were determined during ozone (O(3)) exposure in Arabidopsis. Rosettes were treated with 0.15 μL L(−1) O(3) for 6 h d(−1) for 14 d. O(3)-treated leaves began to yellow after 10 d of exposure, whereas yellowing was not apparent in control leaves until d 14. Transcript levels for eight of 12 senescence related genes characterized showed induction by O(3). SAG13 (senescence-associated gene), SAG21, ERD1 (early responsive to dehydration), and BCB (blue copper-binding protein) were induced within 2 to 4 d of O(3) treatment; SAG18, SAG20, and ACS6 (ACC synthase) were induced within 4 to 6 d; and CCH (copper chaperone) was induced within 6 to 8 d. In contrast, levels of photosynthetic gene transcripts, rbcS (small subunit of Rubisco) and cab (chlorophyll a/b-binding protein), declined after 6 d. Other markers of natural senescence, SAG12, SAG19, MT1 (metallothionein), and Atgsr2 (glutamine synthetase), did not show enhanced transcript accumulation. When SAG12 promoter-GUS (β-glucuronidase) and SAG13 promoter-GUS transgenic plants were treated with O(3), GUS activity was induced in SAG13-GUS plants after 2 d but was not detected in SAG12-GUS plants. SAG13 promoter-driven GUS activity was located throughout O(3)-treated leaves, whereas control leaves generally showed activity along the margins. The acceleration of leaf senescence induced by O(3) is a regulated event involving many genes associated with natural senescence.